Direct Photolithography of WOx Nanoparticles for High-Resolution Non-Emissive Displays - Chang Gu; Guojian Yang; Wenxuan Wang; Aiyan Shi; Wenjuan Fang; Lei Qian; Xiaofei Hu; Ting Zhang; Chaoyu Xiang; Yu-Mo Zhang (Nano-Micro Letters)
Highlights Direct photolithography of electrochromic WOx nanoparticles via in situ photo-induced ligand exchange is proposed and demonstrated. The highest resolution among inorganic electrochromics (< 4 µm) is achieved, which is promising in high-resolution non-emissive displays. The as-prepared device exhibits highly remarkable performance including rapid response, high coloration efficiency and durability.